Incidence of anorrectal anomalies in a large mining area: a comparative study between the micro-region of óbidos and the national territory in the period of 2011-2020 (Research, Society and Development, 2023)
Anorectal Anomalies (AAR) still have no defined cause. They can be detected early through imaging tests, providing health professionals with essential information for the adoption of consistent clinical conduct, aiming at a better quality of life for the patient. The high incidence of AAR in regions contaminated by heavy metal residues makes it possible to carry out studies on the subject. Thus, this present study has as main objective to verify the incidence of AAR in places that use toxic products in mining, in live births, between the years 2016 to 2020, comparing with the incidence throughout the national territory within its due proportions of birth by region. This is a descriptive, analytical, retrospective and quantitative analysis epidemiological study. Public domain data were used, which were collected through the TABNET application of the Department of Informatics of the Unified Health System (DATASUS). Data were collected from the Notifiable Diseases Information System (SINAN). There is a need for more studies that address the relationship between the presence of heavy metals in the environment and the appearance of anomalies related to bioaccumulation. Research related to this topic is essential as it proposes viable solutions for the removal of such contaminants, in addition to the adoption of public policies that aim to minimize the impacts of diseases resulting from pollution on the communities present around.